Incidence of back pain from initial presentation to 3 years of follow-up in subjects with untreated adolescent idiopathic scoliosis - Lau, Kenney Ki Lee; Kwan, Kenny Yat Hong; Cheung, Jason Pui Yin; Wong, Janus Siu Him; Shea, Graham Ka Hon; Law, Karlen Ka Pui; Cheung, Kenneth Man Chee (Spine deformity, 2024)
Background Although back pain may be present in subjects with adolescent idiopathic scoliosis (AIS), its natural history is unknown. Therefore, this study evaluated the incidence of back pain in scoliotic adolescents longitudinally. Methods This retrospective analysis examined prospectively collected pain subscale data of the Scoliosis Research Society questionnaire between the initial presentation and up to 3 years of follow-up. Consecutive subjects with AIS aged 10–18 at baseline managed by observation within the study period were included. Study subjects with at least one time point of follow-up data were considered. Alternatively, a group with physiotherapy-treated was also included for comparison. Results We enrolled 428 subjects under observation. The incidence of back pain among study subjects was 14.7%, 18.8%, and 19.0% for the first year, second year, and third year of follow-up, respectively. Most experienced mild pain (1 out of 5 points) throughout the study. Neither incidence nor intensity of pain significantly differed between subjects under observation and received physiotherapy. Additionally, study subjects with a new onset of back pain had poorer function, self-image, and mental health scores than those without pain. Conclusion We investigated the incidence of back pain longitudinally in subjects suffering from AIS. Further validation of the current results is warranted.